SYSTEMATIC LITERATURE REVIEW: DETERMINANTS OF THE SOCIAL ENTREPRENEURIAL INTENTION - Imran Fauzi (SOSIOEDUKASI, 2026)
Amid the complexity of global social challenges such as social inequality, economic crises, and the demands of sustainable development, Social Entrepreneurial Intention (SEI) has garnered increased attention in the entrepreneurship literature, particularly in recent years. Although the number of studies on SEI continues to rise, the empirical findings remain diverse, vary across theories and methodologies, and have not yet been systematically synthesized. The objective of this article is to conduct a Systematic Literature Review (SLR), which will comprehensively map and synthesize the development of SEI research. The literature search process utilized the Scopus database in accordance with the PRISMA guidelines. The search yielded 80 journal articles that met the inclusion criteria for further analysis. This article focuses on annual publication trends, the geographical distribution of research, journal classifications, theoretical foundations, methodological approaches, and the types of populations used in previous SEI studies. The synthesis results indicate that since 2019, SEI research has increased significantly, with countries in Asia—particularly Vietnam, China, and Bangladesh—dominating the SEI research landscape. Theoretically, the most commonly used frameworks to explain the formation of SEI are the Theory of Planned Behavior and the Social Cognitive Career Theory. As conceptual complements, other models, such as the Social Entrepreneurial Intention Model by Mair and Noboa and the Entrepreneurial Event Model, are used more sparingly. Methodologically, quantitative survey-based approaches using SEM and PLS-SEM remain dominant, while qualitative and mixed-method approaches remain relatively scarce. Furthermore, most studies use students as subjects, which limits generalizability. This article contributes by providing a structured mapping of the SEI literature, identifying theoretical, methodological, and contextual gaps, and formulating directions for future research relevant to contemporary social challenges, including digital transformation and demands for social inclusivity.